The role of epithelial-mesenchymal transition in regulating radioresistance. (June 2020) - Zhou, Suna; Zhang, Mingxin; Zhou, Chao; Wang, Wei; Yang, Haihua; Ye, Wenguang
Graphical abstract: Abstract: Cancer patients with different stages can benefit from radiotherapy, but there are still limited due to inherent or acquired radioresistance. The epithelial-mesenchymal transition (EMT) is a complex biological process that is implicated in malignant characteristics of cancer, such as radioresistance. Although the possible mechanisms of EMT-dependent radioresistance are being extensively studied, there is a lack of a clear picture of the overall signaling of EMT-mediated radioresistance. In this review, we highlight the role and possible molecular mechanisms of EMT in cancer radioresistance, in particular to EMT-associated signaling pathway, EMT-inducing transcription factors (EMT-TFs), EMT-related non-coding RNAs. The knowledge of EMT-associated mechanisms of radioresistance will offer more potent therapy targets to improve the radiotherapy responses.